Lessons Learned from Journey Mapping in Health Care. Issue 1 (September 2019) - Maddox, Kyle; Baggetta, Donna; Herout, Jennifer; Ruark, Kurt
The Department of Veterans Affairs' Human Factors Engineering team recognizes the value of journey maps as a means for communication among stakeholder groups and develops maps to showcase the experience of users with health services and technology systems. The uniqueness of health care environments caused difficulties in following available trade guidance for creating journey maps. Anticipating that other Human Factors Engineers working in health care settings will encounter similar challenges, this paper showcases our lessons learned while creating two distinct journey maps and offers a process for constructing journey maps in health care environments. We learned to selectively limit the content of journey maps, ensure design quality by utilizing a template and rubric, and apply alternate approaches for data gathering. Our improved process includes steps to partner with stakeholders, produce a journey map framework and confirm it with user research, and visualize findings in the completed journey map.